ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT. - Veren Gunawan; Julianti Sjarief (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This study aims to analyze the effect of profitability, leverage, and company size on the disclosure of sustainability reports in energy and materials sector companies listed on the Indonesia Stock Exchange in the period 2016 to 2020. The analytical method used in this study is the descriptive analysis method and multiple linear regression analysis, where the data is processed using the Statistical Package for the Social Sciences version 25 program. The results of this study indicate that profitability has no effect on the disclosure of sustainability reports, while leverage and firm size have a positive effect and direction on the disclosure of the sustainability report.